'Scatter-gun' or 'Follow-the-leader' behaviour: international strategies of the high-tech SMEs. (21st October 2009) - Sedoglavich, Vesna; Akoorie, Michele E.M.; Pavlovich, Kathryn
The aim of this study was to examine the internationalisation process high-tech SMEs. Using Ansoff's Matrix, it was found that the most common market growth strategies were market penetration, product development and market development, respectively. Firms were able to modify and sell their products in the existing markets, and to sell the current product range in the new geographic segments. Companies can increase their chances of success if they combine future orientation with organisational adaptability and flexibility. The results reveal the importance of having strong networks throughout the hole process of internationalisation for a long-term survival of high-tech SMEs.